2021
DOI: 10.1186/s12877-021-02074-4
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime prevalence of polyvictimization among older adults in Sweden, associations with ill-heath, and the mediating effect of sense of coherence

Abstract: Background Experiences of violence and abuse is a prominent part of the life history of many older adults and is known to have negative health effects. However, the importance of multiple victimization over the life course, e.g., lifetime polyvictimization, is not well investigated in this age group. The objective of this study was to investigate the prevalence of lifetime physical, emotional, and sexual victimization as well as polyvictimization among older adults in Sweden. We explored backgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 55 publications
(38 reference statements)
4
27
0
Order By: Relevance
“…Previous life experiences are important not only for understanding the individual’s unique vulnerability to abuse, but also for considering the victim’s individual strengths and resources when designing interventions and the prevention of elder abuse [ 35 ]. Hence, our results agree well with previous findings that a life-course perspective is essential when trying to understand the causes and consequences of elder abuse [ 6 8 ]. However, our findings also underline that abuse occurs in a context, and factors on all levels of the socioecological model influence the experience of abuse, e.g., ageist attitudes and dysfunctional care organizations described further on.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Previous life experiences are important not only for understanding the individual’s unique vulnerability to abuse, but also for considering the victim’s individual strengths and resources when designing interventions and the prevention of elder abuse [ 35 ]. Hence, our results agree well with previous findings that a life-course perspective is essential when trying to understand the causes and consequences of elder abuse [ 6 8 ]. However, our findings also underline that abuse occurs in a context, and factors on all levels of the socioecological model influence the experience of abuse, e.g., ageist attitudes and dysfunctional care organizations described further on.…”
Section: Resultssupporting
confidence: 92%
“…Elder abuse is associated with various adverse health outcomes including psychosocial distress, morbidity, and mortality [ 1 ]. Exposure to more than one type of abuse or by more than one perpetrator is called poly-victimization, and this common condition is generally associated with even worse health outcomes than single exposure to abuse [ 5 , 6 ]. It is also increasingly acknowledged that elder abuse is associated with previous experiences of violence in childhood and adulthood, motivating a life-course perspective in research on elder abuse [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stronger sense of coherence meant better physical and mental health and more use of mature defence mechanisms [ 4 ]. Strong sense of coherence has a role in mediating recovery from substantial stressors such as poly-victimization [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, most studies have typically focused on the effects of exposure on single-type elder mistreatment, and multi-type mistreatment has received little attention in the literature. The few available studies found that multi-type mistreatment has a much higher risk of adverse physical and mental health consequences [ 12 , 20 ]. In a study by Simmons and Swahnberg [ 20 ], experiencing multi-type elder mistreatment was associated with adverse physical and mental health, while single-type mistreatment was not.…”
Section: Discussionmentioning
confidence: 99%
“…Most of this substantial knowledge mainly focuses on single types of elder mistreatment. While there is some evidence that exposures to multi-type elder mistreatment may be associated with an even higher increased risk of adverse mental health consequences, the area remains substantially understudied [ 12 , 19 , 20 ]. Furthermore, there is very limited research that is focusing on the impact of single- and multi-type mistreatment on mental health in the Korean older population [ 21 ].…”
Section: Introductionmentioning
confidence: 99%